Bovine virus diarrhea - Mucosal disease has been broken out in Indonesia, initially in 1988. Some cattle sera surveyed were serological positive. In this outnreak Bali breed cattle, Brahman Cross, Sahiwal, local Ongole breed, local breed cattle and buffaloes of all ages and of both sexes were affected. Morbidity rate was 0.23 to 30% and mortality rate was 0.02 to 90%. The clinical form of the disease was acute with profuse watery diarrhea as the predominant symptom. The fluid feces was malodorou - F.X. Soesilo (Hemera Zoa, 1991)
Bovine virus diarrhea - Mucosal disease has been broken out in Indonesia, initially in 1988. Some cattle sera surveyed were serological positive. In this outnreak Bali breed cattle, Brahman Cross, Sahiwal, local Ongole breed, local breed cattle and buffaloes of all ages and of both sexes were affected. Morbidity rate was 0.23 to 30% and mortality rate was 0.02 to 90%. The clinical form of the disease was acute with profuse watery diarrhea as the predominant symptom. The fluid feces was malodorous. Some cattle were suffering erosive lesions of the buccal mucosa. Death caused usually by progressive dehydration and weakness. Transmission occurred through direct and indirect contact. Imported cattle were suspected as the source of infection.